50th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2014
DOI: 10.2514/6.2014-3436
|View full text |Cite
|
Sign up to set email alerts
|

Flow Field and Liner Heat Transfer for a Model Annular Combustor Equipped with Radial Swirlers

Abstract: Swirling flows for combustion stabilization, flame confinement, and proper fuel mixing and recirculation are prevalent in gas turbine combustor applications. Modern gas turbines use swirlers to induce strong rotating vortices and recirculation of the combustion gases to enhance combustion efficiency and stability. This study presents an experimental investigation of the flow field and wall heat transfer characteristics inside a model annular combustor equipped with radial swirlers. 2D Particle Image Velocimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Figure 8 and Figure 9 show the time averaged results for the maximum and minimum Reynolds numbers measured at planes A and D. The white outline in the velocity field of plane A indicates , matching the mean location of the shear layers and the stagnation point at the combustor liner wall. Other authors have reported that the normalized impingement location and overall flow field is approximately independent of mass flow after a self-similarity threshold [18,33,34]. The reason for the self-similarity is that the mechanisms that dominate the flow field within the combustor become inertia dominated (viscous effects are negligible).…”
Section: Wherementioning
confidence: 99%
“…Figure 8 and Figure 9 show the time averaged results for the maximum and minimum Reynolds numbers measured at planes A and D. The white outline in the velocity field of plane A indicates , matching the mean location of the shear layers and the stagnation point at the combustor liner wall. Other authors have reported that the normalized impingement location and overall flow field is approximately independent of mass flow after a self-similarity threshold [18,33,34]. The reason for the self-similarity is that the mechanisms that dominate the flow field within the combustor become inertia dominated (viscous effects are negligible).…”
Section: Wherementioning
confidence: 99%
“…This lead to create a large demand on cold air where that will effect on the efficiency of the gas turbine. Gomez Ramirez et al [4] studied the flow field properties into the annular combustor gas turbine with radial swirls. The heat transfer coefficient increased with increasing Reynolds numbers.…”
Section: Introductionmentioning
confidence: 99%